Effects of Different Nutrient Solutions on Yield and Quality Parameters of Rocket Grown in Floating Water Culture - Golgen Bahar Oztekin; Tuğba Uludağ; Yüksel Tüzel; Mahmut Tepecik (Turkish Journal of Agriculture: Food Science and Technology)
This study was conducted in styrofoam trays placed on an aerated nutrient solution in vats in order to determine the effect of different nutrient solutions on rocket plant growth, yield and quality. Seeds of Bengi F1 rocket cultivar were sown into peat as inserting each seed to each hole (17 ccs) of trays with 210 cells (957 plant m-2). Following germination in the germination chamber, seedling trays were moved to a climate controlled greenhouse for adaptation. After emergence, the seedlings were transferred to water culture. The nutrient solution was applied as “full dose” (mg/L: N 150, P 50, K 150, Ca 150, Mg 50, Fe 5.0, Mn 0.50, Zn 0.05, B 0.50, Cu 0.03, Mo 0.02), “half dose” (macro elements reduced by 50%) and “without nutrients” (water). Cultivation was performed in 2 consecutive periods and in each period 3 harvests were done and quality analysis was done on the leaves from the first harvest. Results were given as the mean of two periods. Results showed that plant growth, yield and quality parameters vary depending on the concentration of the nutrient solution. It was observed that as the concentration of nutrient solution decreased, plant growth, biomass, yield values decreased, leaf color and total chlorophyll concentration did not change and while nitrate content decreased, vitamin C content increased. Leaf N, P, K and Fe element contents decreased with half dose, whereas Ca and Mg content did not change. However, there was no statistical difference between full dose and half dose treatments in many measured parameters. When all the data obtained from the study are evaluated together; it is suggested that rocket can be grown in a floating water culture and the dose of macro elements as reduced 50% can be preferred because it reduces the nitrate content, increases the vitamin C content and allows the use of less fertilizers without causing any significant reduction in yield compared with full dose.